# EXERCISE – 4.2

Q1. Give first the step you will use to separate the variables and then solve  the equation:

(i) x – 1 = 0

SOLUTION:-

x-1 +1 = 0 +1

= x = 1

(b) x + 1 = 0

SOLUTION:-

= x + 1 – 1 = 0 – 1

= x = -1

(c)  x – 1 = 5

SOLUTION:-

= x – 1 + 1 = 5 + 1

= x = 6

(d) x + 6 = 2

SOLUTION:-

= x – 1 + 1 = 5 + 1

= x =  6

(d) x + 6 = 2

SOLUTION:-

= X + 6

– 6 = 2 – 6

= X = -4

(E) y – 4 = -7

SOLUTION:-

= y – 4 +4 = -7 + 4

= = y = -3

(f) y – 4 = 4

SOLUTION:-

= y – 4 + 4 = 4 + 4

= y = 8

(g) y + 4

SOLUTION:-

= Y +4 – 4 = 4 – 4

= Y = 0

(H)  y + 4 = -4

SOLUTION:-

= y + 4 – 4 = -4 – 4

= Y = -8

Q2. Give first the step you will use to separate the variable and then solve the equation:

(a) 3 L = 42

SOLUTION:-

= L = 42/3

= L = 14

(B) B/2 = 6

SOLUTION:-

B = 6 X 2

B = 12

(C) P/7 = 4

SOLUTION:-

P = 4 X 7

`P = 28

(d) 4x = 25

SOLUTION:-

= x = 25/4

= x = 5.1

(e) 8y = 36

SOLUTION:-

= y = 36/8

= y = 4.5

(f) z/3 = 5/4

Solution:-

= z = 15/4

= z = 3.75

(g) a/5 = 7/15

SOLUTION:-

= a = 35/15

= a = 7/3

= a = 2.9

(h) 20t = -10

SOLUTION:-

= t = = -1/2

Q3.Give the steps you will use to separate the variable and then solve the equation:

(a) 3n – 2 = 46

SOLUTION:-

3n = 46 +2

3n = 48

n = 48/3

n = 16

(b) 5m + 7 =17

SOLUTION:-

5m = 17 – 7

5m = 10

m = 10/2

m = 5

(c) 20p/3 = 40

SOLUTION:-

= 20p = 120

= p = 120/20

= p = 6

(d) 3p/10 = 6

SOLUTION:-

= 3p = 6 x 10

= 3p = 60

= p = 60/3

= p = 20

Q4. Solve the following equations:

(a) 10p=100

SOLUTION:-

= 10p = 100

= p = 100/10

= p = 10

(b) 10p + 10 = 100

SOLUTION:-

= 10p = 100-10

= 10 p = 90

= p = 9

(c) p/4 = 5

SOLUTION:-

= p = 20

(d) –p/3 = 5

SOLUTION:-

= -P = 15

(E) 3p/4 = 6

SOLUTION:-

= 3p = 24

= p = 24/3

= p = 8

(f) 3s = -9

SOLUTION:-

= s = -9/3

= s = -3

(g) 3s + 12 = 0

SOLUTION:-

= 3s = -12

= s = -4

(h) 3s = 0

SOLUTION:-

= s = 0

(i) 2q = 6

SOLUTION:-

q = 6/2

q = 3

(j) 2q – 6 = 0

SOLUTION:-

= 2q = 6

= q = 6/2

= q = 3

(k) 2q + 6 = 0

SOLUTION:-

= 2q = -6

= q = -6/2

= q = -3

(i) 2q + 6 = 12

SOLUTION:-

= 2q = 12-6

= 2q = 6

= q = 6/2

= q = 3